Non-polar components in PM2.5 increase matrix remodeling of CRS by up-regulating CEMIP in nasal fibroblasts - Zhou, Jiayao; Zhu, Ying; Hu, Huilin; Tang, Ru; Zhang, Shiyao; Gu, Yuelong; Mao, Song; Pu, Shilei; Lin, Hai; Zhao, Yue; Li, Zhipeng; Zhang, Weitian (Frontiers in Genetics, 2025)
BackgroundFine particulate matter (PM2.5) is harmful to respiratory health and can lead to chronic rhinosinusitis (CRS). But how its components lead to CRS by affecting the function of nasal fibroblasts remains unclear.MethodsIn this study, polar organic components (P-OC) and non-polar organic components (N-OC) isolated from PM2.5 were used to intervene human nasal fibroblasts (hNFs), respectively. CCK8 assay and LDH assay were used to detect cell viability, and scratch assay was used to detect cell migration ability. Gene expression changes were detected by RNA-sequencing and molecular biology.ResultsP-OC inhibited the viability and migration of hNFs, while N-OC significantly promoted the migration of hNFs. The expression of CEMIP, MMP1 and IL-1β was upregulated after N-OC treatment. CEMIP gene silencing inhibited hNFs migration and the expression of MMP1 and IL-1β. The effect of PAHs exposure on cells was more obvious than n-alkanes.ConclusionN-OC in PM2.5, especially PAHs, can aggravate CRS by activating hNFs through CEMIP. This study provides new ideas for exploring the pathogenic mechanism of air pollution on upper respiratory diseases.